Seasonal Diversity of Arbuscular Mycorrhizal Fungi (AMF) in the Mangrove Forests of Bakkhali, Sundarban, India: 10.32526/ennrj/22/20240042 - Paul, Supriti; Parkash, Vipin; Kaundal, Ranjna; Dhara, Bikram; Thapa, Meghna; Mitra, Arup Kumar (Environment and Natural Resources Journal, 2024)
Mangroves, despite thriving at the fringes of habitat tolerance in coastal regions, stand out as one of the world’s most highly productive ecosystems. This study delves into the remarkable symbiotic relationship between mangroves and arbuscular mycorrhizal fungi (AMF). Specifically, it assesses seasonal diversity in six true mangrove species and four associated species, situated in Henry’s Island, Bakkhali, India. Spore density and root colonization were examined across different seasons. The highest spore density was observed in Heritiera fomes (a timber-producing mangrove) during the post-monsoon season, followed by pre-monsoon and monsoon periods. Root colonization was notably prominent in Ceriops tagal (Indian mangrove), Bruguira gymnorrhiza (Oriental mangrove), and Sonneratia alba (flowering evergreen mangrove) during both pre- and post-monsoon seasons. This study unveiled a rich fungal diversity, with a total of 60 AMF species belonging to 13 genera. Among these, the genus Glomus emerged as the dominant group, with species such as G. deserticola along with another genus Rhizophagus intraradics displaying widespread distribution. Notably, Glomus consistently ranked as the most prevalent genus throughout the year, indicating its remarkable adaptability and strong dispersal capacity in both true and associate mangrove plant species. This research sheds light on the seasonal dynamics of AMF associations in mangrove ecosystems, emphasizing the significance of Glomus as a key player in this symbiotic relationship. These findings contribute to our understanding of the ecological intricacies within mangrove habitats and highlight the adaptability of certain AMF genera to varying environmental conditions.